Antenatal Care - How to ensure quality! - Lubna Ejaz (Journal of Rawalpindi Medical College)
Antenatal care (ANC) improves maternal and newborn health by providing a platform for important healthcare services, including health promotion, primary and secondary prevention by vaccination and screening, timely diagnosis & prompt treatment of various obstetrical and medical complications, which may arise or aggravate during pregnancy. Antenatal care substantially contributes to preparedness for labor and postnatal period 1. Healthcare workers should effectively communicate with pregnant women about their physiological, psychological, and sociocultural issues and provide medical, emotional, psychological, financial, and social support during this vulnerable time period 2, 3. Previously, the quality of ANC was assessed by the number of antenatal visits (ANVs) of a pregnant woman with healthcare providers (contact coverage), but now this indicator of the quality of ANC is no longer accepted because it measures contact frequency without looking into the content of the care actually received during ANVs. Discerning the true picture of ANC quality demands the details of each ANV about the four essential parameters including: WHO recommended indicators, effective utilization of health services, doctors’ performance, and patients’ compliance4. WHO has published widely accepted recommendations for ANC, including suggestions for appropriate contact (frequency and timing between clients and the health system) and content (screening and management) based on evidence of effectiveness5. Measuring effective coverage of essential ANC interventions is more comprehensive than just counting the number of ANVs for assessing the ANC quality.